New hosts and the second record of Erythraeus (Zaracarus) lancifer (Trombidiformes: Erythraeidae) - Masoud Hakimitabar; Vahid Rahiminejad; Ahmad Nadimi; Elnaz Fadaei (Persian Journal of Acarology)
The larvae of the Erythraeidae are parasites of various arthropods, including insects and spiders whereas postlarval erythraeids are predators (Gerson et al. 2003). Erythraeus larvae are divided into two subgenera on the basis of the ASens which inserted in sclerotized and angled socket which in Zaracarus and without sclerotized and angled socket in Erythraeus (Xu et al. 2019). There are 28 larval species of Zaracarus which are distributed in different countries of Asia (Indonesia, Iran, Pakistan, China), Europe (Bosnia and Hercegovina, Bulgaria, Croatia, Greece, Hungary, Montenegro, Turkey, Poland, Spain, Italy, Ukraine, Cyprus) and Africa (Ethiopia), There is not any record of this subgenus from Nearctic, Neotropical and Australian regions. Among them, E. (Z.) budapestensis Fain & Ripka, 1998 [syns.: E. (Z.) hamedanicus Khanjani, Mirmoayedi, Nahad & Fayaz, 2010; E. (Z.) preciosus Goldarazena & Zhang, 1998; were collected from 10 countries (Mąkol and Wohltmann 2012, 2013; Xu et al. 2019).